Pemanfaatan Teknologi Dalam Strategi Pembelajaran Menulis Teks Ulasan - La Alu; Wayan Pageyasa; Nurul Haeniah (Perhimpunan Ahli Teknologi Informasi dan Komunikasi Indonesia, 2024)
The capacity to compose review texts is an essential talent in language acquisition, necessitating profound comprehension, critical evaluation, and the capability to articulate concepts methodically. This study seeks to assess the effect of employing technology in instructional methods for composing review texts among eighth-grade students. The study employed a quasi-experimental design utilizing pre-test and post-test methodologies, involving 30 students as participants. The data were evaluated utilizing paired t-test statistical analysis and categorized according to skill levels. The results demonstrated a notable enhancement in the average post-test scores relative to the pre-test scores. Sixty-three point thirty-three percent of pupils were classified in the medium category, exhibiting notable score improvements within this cohort. Technology has been demonstrated to assist students in understanding text structures, rectifying errors, and enhancing the overall quality of their writing. Nevertheless, certain pupils encountered difficulties in effectively leveraging technology. This study underscores the need of incorporating technology into writing teaching to improve students' literacy skills